PENINGKATAN RELIABILITAS, DAYA TANGGAP, DAN JAMINAN PADA KUALITAS LAYANAN STARINDO HEALTHY GROUP - Merry Tandhia (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2016)
The purpose of this research is to improve the reliability, responsiveness, and assurance aspects of Starindo Healthy Group. The five informants in this research are two Starindo Healthy Group consumers, two similar companies, and one marketing expert. Semistructured interview is used as data collection method, while descriptive analysis is used to analyze the research data. Using this approach, the data analysis process is divided into three phases, namely data reduction, data presentation, and conclusion drawing. Research results suggest that the service quality of Starindo Healthy Group; which is represented by reliability, responsiveness, and assurance variables; is already good. However, the company's service quality can be made better with more accurate delivery estimation time and more competent courier. Additionally, the company should also consider using digital technology to deliver invoice and taking order, maintaining and monitoring work standards, and conducting regular evaluation on service quality.